Korean Sinitic Poetry from Ancient Times to 1945: Si in the East - Lee, Jang Wu,; Lee, Ji-Eun,; McCann, David, (Asian Studies E-Books Online, Collection 2024., 2024)
Korean Sinitic Poetry from Ancient Times to 1945 : Si in the East offers a ground-breaking introduction to the oral performative aspect of Korean Sinitic poetry ( hansi 漢詩). The anthology introduces 51 representative works of Korean Sinitic poetry from the 9th to early 20th century including 9 by women poets. Each poem is discussed with ample notes on allusions and expressions, sounds and verbal glossing ( hyŏnt'o ), and commentaries that look beyond the geographical boundary of Korea. Overview essays offer cultural and literary history in a broader East Asian context, and detailed linguistic guides emphasize the musicality and orality of this treasured literary tradition.